Dynamic Capabilities, Organizational Culture and Competitive Advantage : Evidence from Agriculture Cooperatives in China - Qristin Violinda; Sun Jian (APMBA (Asia Pacific Management and Business Application), 2016)
This paper aims at exploring the contributions of dynamic capabilities and organizational culture in the competitive advantage of agriculture cooperatives in China.This study has used a structural equation model (PLS-SEM) to explore a theoretical model which links various dynamic capabilities, organizational culture and competitive advantage. Empirical confirmation is given by simple random sampling and collected data from 201 agriculture cooperatives in China. This study finds that both dynamic capabilities and organizational culture of the cooperatives in China contribute significant and positiveeffect to their competitive advantage as well.